Purchase Intention in TikTok Short-Form Videos: The Roles of Engagement, Product Relevance, and Desire to Postpone Closure - Adinda Fauzah Z N; Dien Mardhiyah; Sri Hartini; Fela Dila Mai Charolin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study analyzes the influence of social systems and technical systems on purchase intention, by examining in more depth the role of engagement, desire to postpone closure, and product relevance intention on the TikTok social commerce platform. TikTok is one of the leading platforms with more than 1 billion users that combines social media and e-commerce, allowing users to discover and purchase products through short-form videos. The research method used is a quantitative approach with an explanatory research design, involving 167 respondents selected using purposive sampling. The results of this study indicate that entertainment and social interaction have a positive and significant effect on engagement, product visibility and recommendations have a positive and significant effect on desire to postpone closure. Meanwhile, entertainment and social interaction do not have a significant effect on the desire to postpone closure. Engagement and desire to postpone closure also do not have a significant effect on purchase intention. Product relevance as a moderating variable is also unable to moderate the relationship between recommendations, either on desire to postpone closure or purchase intention. This study provides valuable insights for marketers and advertisers in designing effective marketing strategies on the TikTok platform.